The Determination of Development Priorities Road Infrastructure at “Dinas Pekerjaaan Umum dan Penataan Ruang Kabupaten Balangan” Using AHP and Bayes Methods - Haderiansyah Haderiansyah; Deni Mahdiana; Ade Davy Wiranata; Mirza Sutrisno (Jurnal Riset Informatika, 2023)
The construction industry is a significant part of the gross domestic product of any country, and its success can lead to the long-term economic and social development of lives in general. Many studies have found a positive link between public infrastructure and the economy. Infrastructure investment directly affects economic growth. Well-designed infrastructure will have long-term financial benefits. The Ministry of Public Works and Housing (Pekerjaan Umum dan Perumahan Rakyat / PUPR) has played an essential role in strengthening the monitoring and evaluation of the implementation of infrastructure development by local authorities, including making the right policies in determining infrastructure development priorities. The Analytical Hierarchy Process (AHP) and Bayes method were used in this study. First, we used AHP to derive independent weights for criteria. Then, we determined the closeness between priorities to produce a sequence of infrastructure development priorities. Based on the results, using Analytical Hierarchy Process (AHP) and Bayes Method showed that Lampihong-Panaitan, Halong-Tabuan, and Bihara-Tariwin roads are Priorities for development. Then the Wangkili-Pudak road, and finally, the Awayan-Bihara. Decision support systems using the AHP and Bayes methods can determine priorities for road infrastructure development at the Office of Public Works and Public Housing in Balangan Regency.